Novel Adiposity Indices Are Associated With Poor Prognosis in Heart Failure With Preserved Ejection Fraction Without the Obesity Paradox - Shuai Zhang; Panpan Xu; Tianhao Wei; Changjiang Wei; Yanling Zhang; Huixia Lu; Cheng Zhang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background There is limited study that illuminates the relationship between obesity indices and prognosis in patients with heart failure with preserved ejection fraction, nor has it been examined whether the obesity paradox persists when using these metrics. Methods and Results This study is a post hoc analysis of data from the TOPCAT (Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist) trial. A total of 3114 individuals were included in our final analysis, and a total of 481 (15.4%) all‐cause deaths, and 389 (12.5%) heart failure hospitalizations were recorded. In a multivariable Cox regression model, compared with patients with a body mass index (BMI) <24.9 kg/m2, those with a BMI of 25.0–29.9, 30.0–34.9, and 35–39.9 kg/m2 were associated with a decreased risk of all‐cause death, with hazard ratio (95% CI) of 0.59 (0.45–0.78), 0.61 (0.46–0.82), and 0.66 (0.47–0.92), respectively. Conversely, patients with a BMI ≥40 kg/m2 showed an increased risk of heart failure hospitalization, compared with BMI <24.9 kg/m2. Furthermore, patients in the highest quintile of obesity indices exhibited a significantly elevated hazard ratio for both all‐cause death and heart failure hospitalization, compared with the lowest quintile. Conclusions An elevated BMI over a certain range was associated with a reduced risk of all‐cause death in heart failure with preserved ejection fraction, displaying a U‐shaped relationship, with no mortality reduction observed in cases of extreme obesity. In contrast, higher values of novel obesity indices were positively correlated with all‐cause death and heart failure hospitalization without the obesity paradox.